Factors influencing the adoption of Touch' n go(TNG) ewallet among consumers in Malaysia - Lim, Si Ting (2024)
The research study are developed to investigate the factors influencing the adoption of Touch’n Go (TNG) among consumer in Malaysia. The main concern of this study will be around the identifies factors includes perceived security, perceived usefulness, consumer’s attitude, and social influence. There are four hypothesisconstructed in order to study and generate comprehensive result.